Recent advances in the transition metal-catalyzed twofold oxidative C–H bond activation strategy for C–C and C–N bond formation - Cho, Seung Hwan; Kim, Ji Young; Kwak, Jaesung; Chang, Sukbok (Chemical Society reviews, 2011)
The direct functionalization of heterocyclic compounds has emerged as one of the most important topics in the field of metal-catalyzed C-H bond activation due to the fact that products are an important synthetic motif in organic synthesis, the pharmaceutical industry, and materials science. This critical review covers the recent progresses on the regioselective dehydrogenative direct coupling reaction of heteroarenes, including arylation, olefination, alkynylation, and amination/amidation mainly utilizing transition metal catalysts (113 references).